The future of veterinarians in dairy herd health management - Silva, João António Martins Cannas da (2012)
The future of the Veterinary Practice in Dairy Health Management has changed and will change more drastically from our point of view in the next years. The consumer’s pressure and the Media are more and more concerned about animal welfare, traceability of animal products and safety of products of animal origin. On the other hand the Farmers in Europe have to produce under strong rules (competing with other countries outside Europe), which are normally very expensive to put in practice, and the veterinarians should adapt their knowledge to the new challenges, because without their work and cooperation, dairy farming will have no future. In that sense, the old veterinary practice has to go in other ways, otherwise the Veterinarians will loose clients and the animal population in Europe will be reduced. The Dairy farmers will ask for support in other areas besides clinical: efficacy, management, welfare, profitability, nutrition, prophylaxis, economics, reproduction, environmental protection, grassland management, etc. Cattle practitioners should be able to give answers in several subjects and this sets the challenge to our profession - Veterinary preparation has to be very strong in single animal species, particularly in Dairy or beef cows. The cattle practitioner has to look beyond, but he should never forget that “the single animal” has to be looked at as one unit of the herd, which means that without a very good knowledge of the single animal he will be insufficiently prepared to solve herd problems, and the Herd is the sum of several animals. We all know that very often one single animal allows us to implement herd strategies and develop prophylactic programs. We are convinced that the veterinary profession, and in our case the Cattle Medicine should have the ability to evolve, otherwise the Veterinarian as we know him will miss the train in the next years.